'Social media comes with good and bad sides, doesn't it?' A balancing act of the benefits and risks of social media use by young adults with long-term conditions. (September 2021) - Wilson, Ceri; Stock, Jennifer
Young adults are frequent users of social media, but the help and hindrance of social media for living well with long-term conditions (LTCs) in young adulthood is little-researched. The aim of this paper was to explore the experiences of social media use amongst young adults with LTCs. Interviews with 15 young adults with LTCs explored their experiences of using social media more broadly and in relation to online health communities. Social media came with both 'good and bad sides' which required a balancing act to manage (overarching theme), as reflected in the following subthemes: (1) Relationships: reducing social isolation versus need for face-to-face contact; (2) Comparisons: normalising versus negative (upward) comparisons; (3) Community: fitting in versus feeling left out; (4) Emotions: inspiring versus distress contagion; and (5) Knowledge: exchanging useful information versus fear of decline. The findings highlight the importance of young adults' self-reflection/awareness of social media's impact on their wellbeing, identifying when limited or increased use may be preferable. Whilst there is a 'good' to social media such as increased feelings of belonging and connection, this should not be the sole focus of future self-management interventions; as its use also contributes to feelings of distress, fear and not fitting in, and participants desire face-to-face contact.